A theory of ellipsis - McShane, Marjorie Joan, 1967- (Oxford University Press, 2005)
This book presents a comprehensive theory of ellipsis that supports the formal, cross-linguistic description of elliptical phenomena. In contrast to earlier work, this study focuses on the interconnected factors that determine whether ellipsis should or should not be used in a given context.